Arched pore structure ceramic fiber aerogel and preparation method thereof
By preparing the ceramic fiber gas gel with the arched hole structure, the problem that the ceramic fiber gas gel is difficult to take into account between the strength and the return of elasticity. need.
Patent Information
- Application Number
- CN202411517454.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Ceramic fiber aerogels are difficult to take into account between strength and resilience. The traditional structural stability, high brittleness and severe powder loss limit their application.
Ceramic fiber gas gel with arched holes structure is used to prepare SIO2 fiber spinning fluid with orthopedic siliconate, deodorite water, phosphate, and polyethylene alcohol, and use electrostatic spinning to prepare ceramic nanofibilities, and through the side Form the arched hole structure towards freezing, and finally prepare gas gel with arched hole structure through drying and high temperature.
The high intensity, good reflection and low thermal conductivity of ceramic fiber gas gel, can maintain stable structure in the environment of long -term large loads, suitable for actual application needs.
Smart Images

Figure CN119019161B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal insulation materials, and in particular relates to a ceramic fiber aerogel with an arched pore structure. The invention also relates to a method for preparing the ceramic fiber aerogel. Background Art
[0002] Ceramic aerogel is a lightweight and efficient thermal insulation material due to its unique nanoporous structure, high porosity, low density and extremely low thermal conductivity. As an emerging high-performance thermal insulation material, aerogel has been used in many fields such as power battery insulation, aerospace thermal protection and industrial building insulation. Traditional ceramic particle aerogels have problems such as poor structural stability, high brittleness and severe powder loss due to their pearl necklace-like structure, which seriously hinders the application of aerogel materials. In order to improve its mechanical properties, nanofibers are used instead of nanoparticles to prepare ceramic fiber aerogels with a three-dimensional mesh structure, which can greatly improve its brittleness. Since the uniform three-dimensional mesh structure can effectively disperse and transfer stress, the ceramic fiber aerogel has good resilience. However, although the ceramic fiber aerogel has good resilience, it also has the problem of low strength.
[0003] At present, the main methods for improving the strength of ceramic fiber aerogels are to combine them with high-strength materials or design pore structures: (1) Composite reinforcement. Kantor et al. (Chemical Engineering Journal. 2022;443:136401.) used polyimide to coat SiO 2 Aerogel. The polyimide component gives the composite material excellent mechanical properties, greatly improving the compression modulus, compression and bending strength. However, the introduction of the organic phase reduces the high-temperature stability of the aerogel. After exposure to temperatures above 200°C, the polyimide aerogel usually undergoes a high degree of volume shrinkage and the aerogel mesoporous structure is destroyed. Bin Yuan et al. (Science China Chemistry. 2016;59(10):1335-41.) composited aluminum hydroxide and cellulose aerogel. Aluminum hydroxide nanoparticles are evenly distributed in the matrix without changing the uniform nanoporous structure of the cellulose aerogel. The addition of aluminum hydroxide can significantly reduce the flammability of cellulose aerogel, but the aerogel still has the disadvantage of high-temperature carbonization. (2) Optimizing the pore structure, such as Si et al. (ACS Applied Materials&Interfaces. 2019;11(38):35333-42) prepared SiO with a lamellar structure by freeze-drying. 2Nanofiber aerogel. The prepared aerogel has a strong structure. It can withstand a pressure of more than 7000 times its own weight without being destroyed. However, its elasticity is not satisfactory. After 500 loading and unloading cycles, the maximum stress is retained by about 70%. In contrast, Dou et al. (ACS Applied Materials & Interfaces. 2019;11(32):29056-64) prepared a honeycomb cell structure SiO 2 / C nanofiber aerogel. SiO 2 The energy loss coefficient of / C nanofiber aerogel at 80% strain is about 0.5, but the strength is low, and the maximum stress is only 4KPa. The layered structure is often stronger, with high strength and low rebound. The cellular structure is more conducive to stress dispersion, with high rebound and low strength. It is difficult for both structures to take into account both strength and resilience. In order to meet the needs of practical applications, a special porous structure that takes into account both strength and resilience must be developed. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a ceramic fiber aerogel with an arched pore structure, so as to achieve a balance among the strength, resilience and thermal insulation performance of the aerogel and meet the needs of actual long-term applications.
[0005] Another object of the present invention is to provide a ceramic fiber aerogel with an arched pore structure.
[0006] The first technical solution adopted by the present invention is a method for preparing a ceramic fiber aerogel with an arched pore structure, which specifically comprises the following steps:
[0007] Step 1: Prepare SiO2 using tetraethyl orthosilicate, deionized water, phosphoric acid and polyvinyl alcohol. 2 Fiber spinning solution, based on SiO 2 The fiber spinning solution was prepared by electrospinning to obtain SiO 2 Ceramic nanofiber membrane;
[0008] Step 2: Prepare an impregnation solution using ethyl orthosilicate, deionized water and acetic acid to form a fixed thickness of SiO 2 The ceramic nanofiber membrane is placed in an impregnation liquid for impregnation;
[0009] Step 3: The impregnated SiO 2 The ceramic nanofiber membrane is placed in a copper mold, and the copper mold is frozen laterally, allowing ice crystals to grow through the cross section of the fiber membrane to construct an arched pore structure;
[0010] Step 4: The SiO 2 The ceramic nanofiber membrane is dried and calcined at a temperature of 700°C for 1 h to obtain a ceramic fiber aerogel with an arched pore structure.
[0011] The first technical solution of the present invention is also characterized in that:
[0012] Preparation of SiO in step 1 2 The fiber spinning solution specifically comprises the following steps:
[0013] S101, mixing tetraethyl orthosilicate, deionized water and phosphoric acid in a mass ratio of 1:1:0.01-0.02, stirring on a magnetic stirrer for 8 hours after mixing, so that the tetraethyl orthosilicate is fully hydrolyzed to uniformly prepare liquid A;
[0014] S102, mixing polyvinyl alcohol and deionized water, wherein the mass fraction of the polyvinyl alcohol after mixing is 8wt% to 12wt%, heating the mixture to 80°C in a water bath and stirring for 0.5h, and obtaining a polymer solution B containing 8wt% to 12wt% PVA after the polyvinyl alcohol is completely dissolved;
[0015] S103, liquid A and liquid B are mixed in a mass ratio of 1:1 and stirred for 4 hours to obtain SiO 2 Fiber spinning solution.
[0016] In step 1, SiO 2 Specifically, the ceramic nanofiber membrane is prepared by using a propulsion speed of 0.6 ml / h to 0.8 ml / h, a spinning spacing of 20 cm, and a pressurized electric field of 17 KV to prepare a precursor fiber, and calcining the precursor fiber at 600°C to 700°C for 2h to 4h in a box furnace to obtain SiO 2 Ceramic nanofiber membrane.
[0017] In step 2, when preparing the impregnation solution, ethyl orthosilicate is added to 30 g of deionized water, and 0.5 g of acetic acid is added at the same time, and the mixture is evenly mixed to obtain the impregnation solution.
[0018] Step 2: Place SiO2 in the impregnation solution 2 Ceramic nanofiber membranes are stacked, SiO 2 The fixed thickness of the ceramic nanofiber membrane is 700 μm~1600 μm, and the immersion time is 6 h.
[0019] The temperature of the lateral freezing in step 3 is -60°C to -140°C, and the insulation time is 10 minutes.
[0020] The drying step in step 4 is to dry the SiO 2 The ceramic nanofiber membrane is placed at a temperature of -30°C to -40°C and a vacuum degree of 1 Pa to 3 Pa and dried for 24 h to 36 h.
[0021] The second technical solution adopted by the present invention is that the ceramic fiber aerogel with an arched pore structure is prepared by the above-mentioned preparation method of the ceramic fiber aerogel with an arched pore structure.
[0022] The beneficial effects of the present invention are:
[0023] (1) The arched pore structure in the ceramic fiber aerogel of the present invention can use the support reaction force generated by the two side support points to offset the bending moment, so that the aerogel pore wall is only subjected to pressure but not tension. 2 When the fiber aerogel is subjected to stress, the pore wall is subjected to pressure on one side and tension on the other side due to the bending moment. The nanofibers on the tension side are very likely to separate and break, which makes the pore structure of the aerogel very easy to be destroyed and fail. Therefore, the ceramic fiber aerogel with an arched pore structure of the present invention can maintain structural stability in a long-term high-load use environment, and has high strength, good resilience and extremely low thermal conductivity.
[0024] (2) The formation of the ceramic fiber aerogel with an arched pore structure of the present invention is achieved by controlling the growth morphology of ice crystals during the freeze casting process. First, the preparation method of the present invention adopts lateral freezing, which is different from the common unidirectional freezing and bidirectional freezing from bottom to top. During lateral freezing, the fiber membrane can inhibit the growth of ice crystals along the thickness direction of the fiber membrane, and the ice crystals show an oriented growth that is strong left and right and weak up and down, making it easier for the ice crystals to form an arched morphology.
[0025] In addition, the preparation method of the present invention realizes the formation of an arched pore structure by controlling the matching of the freezing temperature and the thickness of the fiber membrane. During the freezing process, ice crystals grow by squeezing the fiber membrane, and the fiber membrane hinders the growth of ice crystals. The thicker the fiber membrane, the denser it tends to be, so the thickness of the fiber membrane determines the resistance to ice crystal growth. When the fiber membrane is too thick, the resistance is too large, and the growth of ice crystals along the thickness direction is severely inhibited, forming a layered pore structure; when the fiber membrane thickness is insufficient, the resistance is too small, and the ice crystals grow freely to form a cellular pore structure. The freezing temperature determines the driving force for the growth of ice crystals. When the freezing temperature is too low, the driving force is too large, and the growth of ice crystals is difficult to be inhibited, forming a cellular pore structure; when the freezing temperature is too high, the driving force is too small, and the growth of ice crystals is easily inhibited to form a layered pore structure.
[0026] Only when the driving force and resistance of ice crystal growth are properly matched, the ice crystals show appropriate oriented growth to form an arched pore structure. The arched pore structure prepared by the present invention has good uniformity and high repeatability, and the process is simple, and can be extended to the preparation of other arched pore structure aerogels. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic flow chart of a method for preparing a ceramic fiber aerogel with an arched pore structure according to the present invention;
[0028] Figure 2 It is a schematic diagram of lateral freezing in the method for preparing the ceramic fiber aerogel with an arched pore structure of the present invention;
[0029] Figure 3 Schematic diagram of the arched pore structure of the ceramic fiber aerogel with an arched pore structure of 50 μm in the present invention;
[0030] Figure 4 Schematic diagram of the arched pore structure of the ceramic fiber aerogel with an arched pore structure of 5 μm in the present invention;
[0031] Figure 5 This is a physical picture of the ceramic fiber aerogel with an arched pore structure prepared in Example 1 of the present invention;
[0032] Figure 6 is a compressive stress-strain curve diagram of the ceramic fiber aerogel with an arched pore structure in Example 1 of the present invention;
[0033] Figure 7 is a compressive stress-strain curve diagram of the ceramic fiber aerogel with an arched pore structure in Example 5 of the present invention;
[0034] Figure 8 This is a compressive stress-strain curve of the ceramic fiber aerogel with an arched pore structure according to Example 9 of the present invention. DETAILED DESCRIPTION
[0035] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] The method for preparing the ceramic fiber aerogel with an arched pore structure of the present invention firstly adopts an electrospinning method to prepare a flexible SiO 2 The ceramic nanofiber membrane is then impregnated and stacked in a special copper mold. Lateral freezing is used to allow ice crystals to grow through the cross section of the fiber membrane to construct an arched pore structure. Finally, SiO2 with an arched pore structure is prepared by drying and high-temperature calcination. 2 Aerogel.
[0037] The preparation method of the ceramic fiber aerogel with arched pore structure of the present invention is as follows: Figure 1 As shown, the specific steps include:
[0038] Step 1: Prepare SiO2 using tetraethyl orthosilicate, deionized water, phosphoric acid and polyvinyl alcohol. 2 Fiber spinning solution, based on SiO 2 The fiber spinning solution was prepared by electrospinning to obtain SiO 2 Ceramic nanofiber membrane.
[0039] Step 2: Add ethyl orthosilicate to 30 g of deionized water and 0.5 g of acetic acid, mix well to obtain an impregnation solution, and then add a fixed thickness of SiO 2 The ceramic nanofiber membrane is immersed in an immersion liquid; specifically, the SiO 2The ceramic nanofiber membranes were stacked with a fixed stacking thickness of 700 μm to 1600 μm and an immersion time of 6 h.
[0040] Step three, such as Figure 2 As shown, the impregnated SiO 2 The ceramic nanofiber membrane is placed in a copper mold and the copper mold is frozen laterally at a temperature of -60°C to -140°C for 10 minutes, allowing ice crystals to grow through the cross-section of the fiber membrane to construct an arched pore structure.
[0041] Step 4: The SiO 2 The ceramic nanofiber membrane is dried and calcined to obtain a ceramic fiber aerogel with an arched pore structure.
[0042] Further, in step 1, SiO is prepared 2 The fiber spinning solution specifically comprises the following steps:
[0043] S101, mixing tetraethyl orthosilicate, deionized water and phosphoric acid in a mass ratio of 1:1:0.01-0.02, stirring on a magnetic stirrer for 8 hours after mixing, so that the tetraethyl orthosilicate is fully hydrolyzed to uniformly prepare liquid A;
[0044] S102, mixing polyvinyl alcohol and deionized water, wherein the mass fraction of the polyvinyl alcohol after mixing is 8wt% to 12wt%, heating the mixture to 80°C in a water bath and stirring for 0.5h, and obtaining a polymer solution B containing 8wt% to 12wt% PVA after the polyvinyl alcohol is completely dissolved;
[0045] S103, liquid A and liquid B are mixed in a mass ratio of 1:1 and stirred for 4 hours to obtain SiO 2 Fiber spinning solution.
[0046] Furthermore, in step 1, SiO 2 Specifically, the ceramic nanofiber membrane is prepared by using a propulsion speed of 0.6 ml / h to 0.8 ml / h, a spinning spacing of 20 cm, and a pressurized electric field of 17 KV to prepare a precursor fiber, and calcining the precursor fiber at 600°C to 700°C for 2h to 4h in a box furnace to obtain SiO 2 Ceramic nanofiber membrane.
[0047] Furthermore, the drying in step 4 is specifically to freeze the SiO 2 The ceramic nanofiber membrane is placed at a temperature of -30°C to -40°C and a vacuum degree of 1 Pa to 3 Pa and dried for 24 h to 36 h to obtain an aerogel embryo, and then the dried aerogel embryo is calcined at 700°C in a box furnace for 1 h, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0048] On the other hand, the present invention also provides a ceramic fiber aerogel with an arched pore structure, which is prepared by the above-mentioned method for preparing the ceramic fiber aerogel with an arched pore structure.
[0049] like Figure 3 and Figure 4 As shown, a 50 μm enlarged schematic diagram and a 5 μm enlarged schematic diagram of the ceramic fiber aerogel with an arched pore structure prepared by the present invention are shown. It can be seen from the figure that all the pores inside the aerogel are arched pore structures, and these arched pore structures are not only evenly distributed but also consistent in size.
[0050] In the preparation method of the ceramic fiber aerogel with an arched pore structure of the present invention, there is a matching relationship between the fiber membrane thickness required to form the arched pore structure and the freezing temperature, as shown in the following Table 1, that is, only when a certain fiber membrane thickness matches a specific freezing temperature can an aerogel with an arched pore structure be prepared.
[0051] Table 1 Matching table of fiber membrane thickness formed by arched pore structure and freezing temperature
[0052]
[0053] Example 1
[0054] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0055] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.01, and stirred on a magnetic stirrer for 8 hours to fully hydrolyze TEOS to prepare liquid A; polyvinyl alcohol and deionized water were mixed, and the mass fraction of polyvinyl alcohol after mixing was 8wt%. After mixing, they were heated to 80℃ in a water bath and stirred for 0.5h, and after PVA was completely dissolved, a polymer solution B of 8wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4h to mix evenly to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.6 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 4 h. The precursor fiber was calcined at 700 ° C in a box furnace for 2 h to obtain SiO with a thickness of 700 μm~800 μm. 2 Ceramic nanofiber membrane.
[0056] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0057] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0058] Step 3, lateral freezing to form an arched hole structure;
[0059] After impregnation, SiO 2 The ceramic nanofiber membranes were stacked in a special mold, frozen laterally at -60°C, and kept warm for 10 min.
[0060] Step 4, drying and calcining;
[0061] The aerogel body was then dried at a temperature of -30°C and a vacuum degree of 1 Pa for 36 hours, and the dried aerogel body was calcined in a box furnace at 700°C for 1 hour, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0062] The ceramic fiber aerogel prepared in this embodiment is as follows Figure 5 As shown, aerogel is made of stacked fiber membranes, and its shape and structure are easy to control. It can easily stand on a dandelion and has the characteristic of being ultra-light.
[0063] The ceramic fiber aerogel of this embodiment was subjected to loading-unloading tests under different strains, such as Figure 6 The aerogel shown has ultra-high strength up to 1.6MPa and good elasticity, and can successfully rebound after compression.
[0064] Example 2
[0065] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0066] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.02, and stirred on a magnetic stirrer for 8 hours to fully hydrolyze TEOS to prepare liquid A; polyvinyl alcohol and deionized water were mixed, and the mass fraction of polyvinyl alcohol after mixing was 10wt%. After mixing, they were heated to 80℃ in a water bath and stirred for 0.5h, and after PVA was completely dissolved, a polymer solution B of 10wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4h to mix evenly to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.8 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 4 h. The precursor fiber was calcined at 600 ° C in a box furnace for 4 h to obtain SiO with a thickness of 800 μm~900 μm. 2 Ceramic nanofiber membrane.
[0067] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0068] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2 The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0069] Step 3, lateral freezing to form an arched hole structure;
[0070] The impregnated fiber membranes were stacked in a special mold, frozen sideways at -70°C, and kept warm for 10 min.
[0071] Step 4, drying and calcining;
[0072] Then, the aerogel body was dried at -40°C and vacuum degree of 3 Pa for 24 hours. The dried aerogel body was calcined at 700°C for 1 hour in a box furnace, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0073] Example 3
[0074] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0075] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.01, and stirred on a magnetic stirrer for 8 hours to fully hydrolyze TEOS to prepare liquid A; polyvinyl alcohol and deionized water were mixed, and the mass fraction of polyvinyl alcohol after mixing was 12wt%. After mixing, they were heated to 80℃ in a water bath and stirred for 0.5h, and after PVA was completely dissolved, a polymer solution B of 12wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4h to mix evenly to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.7 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 4.5 h. The precursor fiber was calcined at 700 ° C in a box furnace for 2 h to obtain SiO with a thickness of 900 μm~1000 μm. 2 Ceramic nanofiber membrane.
[0076] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0077] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2 The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0078] Step 3, lateral freezing to form an arched hole structure;
[0079] After impregnation, SiO 2 The ceramic nanofiber membranes were stacked in a special mold, frozen sideways at -80°C, and kept warm for 10 min.
[0080] Step 4, drying and calcining;
[0081] Then, the aerogel body was dried at -35°C and vacuum degree of 2 Pa for 36 hours to obtain the aerogel body. The dried aerogel body was calcined at 700°C for 1 hour in a box furnace, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0082] Example 4
[0083] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0084] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.01, and stirred on a magnetic stirrer for 8 hours to allow TEOS to be fully hydrolyzed and uniformly prepared to obtain liquid A; PVA and deionized water were mixed in a mass ratio of 1:9, and heated to 80°C in a water bath and stirred for 0.5 hours, and after PVA was completely dissolved, a polymer solution liquid B containing 10 wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4 hours to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.6 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 5.5 h. The precursor fiber was calcined at 700 ° C in a box furnace for 2 h to obtain SiO with a thickness of 1000 μm~1100 μm. 2 Ceramic nanofiber membrane.
[0085] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0086] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2 The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0087] Step 3, lateral freezing to form an arched hole structure;
[0088] After impregnation, SiO 2The ceramic nanofiber membranes were stacked in a special mold, frozen laterally at -90°C, and kept warm for 10 min.
[0089] Step 4, drying and calcining;
[0090] Then, the aerogel body was dried at -30°C and vacuum degree of 1 Pa for 36 hours to obtain the aerogel body. The dried aerogel body was calcined at 700°C for 1 hour in a box furnace, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0091] Example 5
[0092] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0093] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.01, and stirred on a magnetic stirrer for 8 hours to allow TEOS to be fully hydrolyzed and uniformly prepared to obtain liquid A; PVA and deionized water were mixed in a mass ratio of 1:9, and heated to 80°C in a water bath and stirred for 0.5 hours, and after PVA was completely dissolved, a polymer solution liquid B containing 10 wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4 hours to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.6 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 6 h. The precursor fiber was calcined at 700 ° C in a box furnace for 2 h to obtain SiO with a thickness of 1100 μm~1200 μm. 2 Ceramic nanofiber membrane.
[0094] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0095] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2 The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0096] Step 3, lateral freezing to form an arched hole structure;
[0097] After impregnation, SiO 2 The ceramic nanofiber membranes were stacked in a special mold, frozen laterally at -100°C, and kept warm for 10 min.
[0098] Step 4, drying and calcining;
[0099] Then, the aerogel body was dried at -30°C and vacuum degree of 1 Pa for 36 hours to obtain the aerogel body. The dried aerogel body was calcined at 700°C for 1 hour in a box furnace, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0100] The ceramic fiber aerogel of this embodiment was subjected to loading-unloading tests under different strains, such as Figure 7 The aerogel shown has ultra-high strength up to 2.4MPa and good elasticity, and can successfully rebound after compression.
[0101] Example 6
[0102] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0103] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.01, and stirred on a magnetic stirrer for 8 hours to allow TEOS to be fully hydrolyzed and uniformly prepared to obtain liquid A; PVA and deionized water were mixed in a mass ratio of 1:9, and heated to 80°C in a water bath and stirred for 0.5 hours, and after PVA was completely dissolved, a polymer solution liquid B containing 10 wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4 hours to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.6 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 6.5 h. The precursor fiber was calcined at 700 ° C in a box furnace for 2 h to obtain SiO with a thickness of 1200 μm~1300 μm. 2 Ceramic nanofiber membrane.
[0104] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0105] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2 The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0106] Step 3, lateral freezing to form an arched hole structure;
[0107] After impregnation, SiO 2 The ceramic nanofiber membranes were stacked in a special mold, frozen laterally at -110°C, and kept warm for 10 min.
[0108] Step 4, drying and calcining;
[0109] Then, the aerogel body was dried at -30°C and vacuum degree of 1 Pa for 36 hours to obtain the aerogel body. The dried aerogel body was calcined at 700°C for 1 hour in a box furnace, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0110] Example 7
[0111] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0112] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.01, and stirred on a magnetic stirrer for 8 hours to allow TEOS to be fully hydrolyzed and uniformly prepared to obtain liquid A; PVA and deionized water were mixed in a mass ratio of 1:9, and heated to 80°C in a water bath and stirred for 0.5 hours, and after PVA was completely dissolved, a polymer solution liquid B containing 10 wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4 hours to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.6 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 7 h. The precursor fiber was calcined at 700 ° C in a box furnace for 2 h to obtain SiO with a thickness of 1300 μm~1400 μm. 2 Ceramic nanofiber membrane.
[0113] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0114] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2 The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0115] Step 3, lateral freezing to form an arched hole structure;
[0116] After impregnation, SiO 2 The ceramic nanofiber membranes were stacked in a special mold, frozen laterally at -120°C, and kept warm for 10 min.
[0117] Step 4, drying and calcining;
[0118] Then, the aerogel body was dried at -30°C and vacuum degree of 1 Pa for 36 hours to obtain the aerogel body. The dried aerogel body was calcined at 700°C for 1 hour in a box furnace, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0119] Example 8
[0120] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0121] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.01, and stirred on a magnetic stirrer for 8 hours to allow TEOS to be fully hydrolyzed and uniformly prepared to obtain liquid A; PVA and deionized water were mixed in a mass ratio of 1:9, and heated to 80°C in a water bath and stirred for 0.5 hours, and after PVA was completely dissolved, a polymer solution liquid B containing 10 wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4 hours to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.6 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 7.5 h. The precursor fiber was calcined at 700 ° C in a box furnace for 2 h to obtain SiO with a thickness of 1400 μm~1500 μm. 2 Ceramic nanofiber membrane.
[0122] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0123] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2 The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0124] Step 3, lateral freezing to form an arched hole structure;
[0125] After impregnation, SiO 2 The ceramic nanofiber membranes were stacked in a special mold, frozen laterally at -130°C, and kept warm for 10 min.
[0126] Step 4, drying and calcining;
[0127] Then, the aerogel body was dried at -30°C and vacuum degree of 1 Pa for 36 hours to obtain the aerogel body. The dried aerogel body was calcined at 700°C for 1 hour in a box furnace, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0128] Example 9
[0129] Step 1: Preparation of SiO 2 Ceramic nanofiber membrane;
[0130] Tetraethyl orthosilicate (TEOS), deionized water and phosphoric acid were mixed in a mass ratio of 1:1:0.01, and stirred on a magnetic stirrer for 8 hours to allow TEOS to be fully hydrolyzed and uniformly prepared to obtain liquid A; PVA and deionized water were mixed in a mass ratio of 1:9, and heated to 80°C in a water bath and stirred for 0.5 hours, and after PVA was completely dissolved, a polymer solution liquid B containing 10 wt% PVA was obtained; liquid A and liquid B were mixed in a mass ratio of 1:1 and stirred for 4 hours to obtain SiO 2 During electrospinning, the precursor fiber was prepared at a propulsion speed of 0.6 ml / h, a spinning spacing of 20 cm, a pressurized electric field of 17 KV, and a spinning time of 8 h. The precursor fiber was calcined at 700 ° C in a box furnace for 2 h to obtain SiO with a thickness of 1500 μm~1600 μm. 2 Ceramic nanofiber membrane.
[0131] Step 2: Impregnation of SiO 2 Ceramic nanofiber membrane;
[0132] Add TEOS to 30g of deionized water and 0.5g of acetic acid. The mass fraction of TEOS is 0.3wt%. Mix well to obtain an impregnation solution. 2 The ceramic nanofiber membrane was added into the impregnation solution and fully immersed for 6 hours.
[0133] Step 3, lateral freezing to form an arched hole structure;
[0134] After impregnation, SiO 2 The ceramic nanofiber membranes were stacked in a special mold, frozen laterally at -140°C, and kept warm for 10 min.
[0135] Step 4, drying and calcining;
[0136] Then, the aerogel body was dried at -30°C and vacuum degree of 1 Pa for 36 hours to obtain the aerogel body. The dried aerogel body was calcined at 700°C for 1 hour in a box furnace, and finally air-cooled to room temperature to obtain a ceramic fiber aerogel with an arched pore structure.
[0137] The ceramic fiber aerogel of this embodiment was subjected to loading-unloading tests under different strains, such as Figure 8 The aerogel shown has ultra-high strength up to 5.5MPa and good elasticity, and can successfully rebound after compression.
[0138] The performance of the ceramic fiber aerogels prepared in Examples 1 to 9 was tested, and the test results are shown in Table 2 below:
[0139] Table 2 Arched pore structure SiO in Examples 1 to 9 2Performance parameters of fiber aerogel
[0140]
[0141] It can be seen from Table 2 that all aerogels have high strength, low thermal conductivity and ultra-low density, which can better bring into play the material properties of aerogels that are lightweight and high-strength.
Claims
1. A method for preparing ceramic fiber aerogel with an arched pore structure, characterized in that: The specific steps include: Step 1, preparing a SiO2 fiber spinning solution by using tetraethyl orthosilicate, deionized water, phosphoric acid and polyvinyl alcohol, and preparing a SiO2 ceramic nanofiber membrane by using an electrospinning method based on the SiO2 fiber spinning solution; Step 2, preparing an impregnation solution by using ethyl orthosilicate, deionized water and acetic acid, and placing a SiO2 ceramic nanofiber membrane of a fixed thickness into the impregnation solution for impregnation; Step 3, placing the impregnated SiO2 ceramic nanofiber membrane into a copper mold, and freezing the copper mold laterally, allowing ice crystals to grow through the cross section of the fiber membrane to construct an arched pore structure; Step 4, drying and calcining the SiO2 ceramic nanofiber membrane after side freezing, the calcination temperature is 700°C, the time is 1h, and the arched pore structure ceramic fiber aerogel is obtained; The temperature of the lateral freezing in step 3 is -60°C to -140°C, and the insulation time is 10 minutes; When preparing the impregnation solution in step 2, ethyl orthosilicate is added into 30g of deionized water, the mass fraction of ethyl orthosilicate is 0.3wt%, and 0.5g of acetic acid is added at the same time, and the mixture is evenly mixed to obtain the impregnation solution; In the step 2, the SiO2 ceramic nanofiber membranes are placed in the impregnation liquid for stacking, the fixed thickness of the stacking is 700 μm to 1600 μm, and the impregnation time is 6 hours.
2. The method for preparing the ceramic fiber aerogel with an arched pore structure according to claim 1, characterized in that: The step 1 of preparing the SiO2 fiber spinning solution specifically comprises the following steps: S101, mixing tetraethyl orthosilicate, deionized water and phosphoric acid in a mass ratio of 1:1:0.01-0.02, stirring on a magnetic stirrer for 8 hours after mixing, so that the tetraethyl orthosilicate is fully hydrolyzed to uniformly prepare liquid A; S102, mixing polyvinyl alcohol and deionized water, wherein the mass fraction of the polyvinyl alcohol after mixing is 8 wt % to 12 wt %, heating the mixture to 80° C. in a water bath and stirring for 0.5 h, and obtaining a polymer solution B containing 8 wt % to 12 wt % of polyvinyl alcohol after the polyvinyl alcohol is completely dissolved; S103, mixing liquid A and liquid B in a mass ratio of 1:1 and stirring for 4 hours to mix evenly to obtain SiO2 fiber spinning solution.
3. The method for preparing the ceramic fiber aerogel with an arched pore structure according to claim 1, characterized in that: In the step 1, the electrospinning method is used to prepare the SiO2 ceramic nanofiber membrane. Specifically, the precursor fiber is prepared at a propulsion speed of 0.6ml / h~0.8ml / h, a spinning spacing of 20cm, and a pressurized electric field of 17KV, and the precursor fiber is calcined at 600℃~700℃ in a box furnace for 2h~4h to obtain the SiO2 ceramic nanofiber membrane.
4. The method for preparing the ceramic fiber aerogel with an arched pore structure according to claim 1, characterized in that: The drying in step 4 is specifically to place the laterally frozen SiO2 ceramic nanofiber membrane at a temperature of -30°C to -40°C and a vacuum degree of 1 Pa to 3 Pa for 24 hours to 36 hours.
5. Arched pore structure ceramic fiber aerogel, characterized in that: The ceramic fiber aerogel with an arched pore structure is prepared by the method for preparing the ceramic fiber aerogel with an arched pore structure as claimed in any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method of ceramic aerogel material with high strength and low thermal conductivity
CN115849949A